2007
DOI: 10.1007/s00431-006-0376-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal smoking on neonatal aortic intima-media thickness, serum IGF-I and IGFBP-3 levels

Abstract: Epidemiological studies have reported associations between a range of cardiovascular risk factors such as smoking and intima-media thickness (IMT). Some reports indicate that the maternal tobacco smoking causes disturbances of the endocrine status of the foetus. There are several potential mechanisms by which insulin-like growth factor I (IGF-I) could modify atherosclerotic processes either locally or in a systemic manner. The aim of this study was to investigate the influence of maternal smoking on neonatal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 43 publications
1
40
2
Order By: Relevance
“…[13][14][15][16][17][18][19][20] Our findings are inconsistent with studies reporting an increase in arterial wall layer thickness in LGA neonates 26,27 but in concordance with previous autopsy studies on SGA neonates. 21 Moreover, our reported arterial layer thicknesses are much thinner than those previously reported, indicating an important difference in methodology attributable improved axial resolution, as recently discussed.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19][20] Our findings are inconsistent with studies reporting an increase in arterial wall layer thickness in LGA neonates 26,27 but in concordance with previous autopsy studies on SGA neonates. 21 Moreover, our reported arterial layer thicknesses are much thinner than those previously reported, indicating an important difference in methodology attributable improved axial resolution, as recently discussed.…”
Section: Discussioncontrasting
confidence: 67%
“…Assessing the vascular phenotype during the early stages of life is necessary for distinguishing longitudinal changes taking place before and after birth. Increased sonographic IMTs [13][14][15][16][17][18][19][20] and normal histological IMTs 21 have been reported in SGA neonates. Smaller arterial lumen diameters (LDs) and reduced microvasculature have also been reported in this population.…”
Section: See Editorial By Gardiner See Clinical Perspectivementioning
confidence: 91%
“…56,57 However, in the UK population, South Asians rather than black AfricanCaribbeans have the lowest mean birth weight and the highest prevalence of low birth weight. 58 Maternal factors, particularly maternal cigarette smoking and low maternal energy intake, are associated with increased offspring cIMT 38,59 and need further exploration. Genetic factors could also be important, although their role remains uncertain.…”
Section: Explanations For Cimt Patternsmentioning
confidence: 99%
“…It was reported that carotid intima-media thickness increased with passive smoking in adults [24][25][26] . Moreover, it was demonstrated that aortic intima-media thickness in newborns exposed to cigarette smoke during pregnancy and carotid intimamedia thickness in young adults increased 9,10 .…”
Section: Volume 59 • Number 1 Ventricular Functions In Children With mentioning
confidence: 99%
“…Although there are many studies showing the effect of the environmental tobacco smoke exposure on the vascular functions in children [8][9][10] , there are no studies showing its effects on the right and left ventricular functions. The objective of this study is to examine the right and left ventricular functions in children with episodic wheezing at the age of 1-3 exposed to ETS.…”
mentioning
confidence: 99%